2005
DOI: 10.1111/j.1348-0421.2005.tb03751.x
|View full text |Cite
|
Sign up to set email alerts
|

XAGE‐1 mRNA Expression in Prostate Cancer and Antibody Response in Patients

Abstract: To evaluate the feasibility of cancer vaccine targeting XAGE‐1, we investigated the expression of 4 XAGE‐1 transcript variants and the humoral immune response to XAGE‐1 in prostate cancer patients. XAGE‐1a, b, c, d mRNA expression was analyzed in 54 prostate cancer specimens and 8 specimens of benign prostate hypertrophy (BPH) by reverse transcription‐polymerase chain reaction (RT‐PCR). The humoral response to XAGE‐1 was investigated in sera obtained from 278 patients with prostate cancer and 40 healthy volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
(14 reference statements)
1
15
0
Order By: Relevance
“…On the basis of the immunocytochemical results Shibayama and Koizumi (3,13) confirmed that normal human prostate epithelial cells specifically express TrkA, but not TrkB or TrkC receptors. Weeraratna et al (14) further demonstrated that TrkA is homogeneously expressed in 60% of primary prostate cancers and 80% of metastatic sites in untreated patients.…”
Section: Discussionmentioning
confidence: 92%
“…On the basis of the immunocytochemical results Shibayama and Koizumi (3,13) confirmed that normal human prostate epithelial cells specifically express TrkA, but not TrkB or TrkC receptors. Weeraratna et al (14) further demonstrated that TrkA is homogeneously expressed in 60% of primary prostate cancers and 80% of metastatic sites in untreated patients.…”
Section: Discussionmentioning
confidence: 92%
“…Transfection with mRNA was shown to be able to present the antigen naturally to not only CD8 but also CD4 T cells (16,17,20). XAGE-1b mRNA was shown to be expressed frequently in non-small cell lung cancer (15/49, 31%), liver cancer (11/19, 58%), and prostate cancer (14/54, 24%), and less frequently in breast cancer (1/20, 5%) (12,18). In lung cancer, a high frequency of XAGE-1b mRNA expression was observed in adenocarcinoma (14/31, 45%) (18).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the dominant XAGE-1 isoform, XAGE-1b, is known to be able to stimulate the immune response of patients suffering from non-small cell lung or prostate cancer (22)(23)(24). In addition, antibody responses to recombinant L552S protein, an alternatively spliced isoform of XAGE-1, were observed in the pleural effusion fluids of lung cancer patients (25).…”
Section: Primermentioning
confidence: 99%